Nighttime Cough Characteristics in Chronic Obstructive Pulmonary Disease Patients - Albertus C. den Brinker; Okke Ouweltjes; Ronald Rietman; Susannah Thackray-Nocera; Michael G. Crooks; Alyn H. Morice (Sensors)
Coughing is a symptom of many respiratory diseases. An increased amount of coughs may signal an (upcoming) health issue, while a decreasing amount of coughs may indicate an improved health status. The presence of a cough can be identified by a cough classifier. The cough density fluctuates considerably over the course of a day with a pattern that is highly subject-dependent. This paper provides a case study of cough patterns from Chronic Obstructive Pulmonary Disease (COPD) patients as determined by a stationary semi-automated cough monitor. It clearly demonstrates the variability of cough density over the observation time, its patient specificity and dependence on health status. Furthermore, an earlier established empirical finding of a linear relation between mean and standard deviation of a session’s cough count is validated. An alert mechanism incorporating these findings is described.